População e território: migração brasileira de nordestinos para o município de Ipameri (GO) entre 1990 e 2018 - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The present work seeks to comprehend by a territorial bias, the migration of northeastern population to the municipality of Ipameri (GO), in the period established between 1990-2018. Thus, to realize this objective, in a qualitative approach, the methodology was based on theoretical research, documentary research and field research. Therefore, as population phenomenon, in a geographical analysis, the migration raises the deterritorialization of migrants from their home territory and consequently, the reterritorialization in a new territory. To this end, in the area quality of expulsion, in the Northeast, material and imaterial factors are responsible by leaving the population of your birth Federation Unit (UF), equally, material and imaterial factors cause the arrival of the northeastern in Ipameri (GO), basin of attraction. In view of this, the northeastern migrant resident in Ipameri (GO) experiences a multiterritoriality, whereas, when the individual goes through the forfeit and reconstruction of territory, he configures his identity according to the cultural, economic and political experiences from the space where he lived/lives.
Population and territory: Brazilian northeastern migration to the municipality of Ipameri (GO) between 1998 and 2018
Keywords: Migração; Nordeste; Ipameri (GO); Desterritorialização; Reterritorialização; Multiterritorialidade; Migration; Northeast; Deterritorialization; Reterritorialization; Multiterritoriality; GEOGRAFIA::GEOGRAFIA HUMANA